The Problem of Consciousness and its Origin in Vasily Sesemann’s Manuscripts - Jonkus, Dalius (Problemos, 2021)
The purpose of this article is to analyse the concept of consciousness in Vasily Sesemann’s manuscripts. Sesemann studied consciousness, describing it as an intentional experience and rejecting its naturalistic explanations. Sesemann revealed the irreducibility of life to physiological or chemical processes and at the same time rejected the dualistic opposition of spirit and matter, soul and body. In the manuscript text “Self-knowledge, self-consciousness and objectification” the philosopher explores the relationship of consciousness with self-consciousness and the subconscious, as well as various forms of objectification of consciousness. This manuscript can be attributed to a group of manuscript texts that discuss the origin of consciousness and the metaphysical relationship between matter and spirit. In the article, I will first discuss the relationship between Sesemann’s concept of consciousness and the philosophy of nature. Second, I will examine how Sesemann understands the relationship between consciousness and self-consciousness and the objectifications of consciousness. Third, I will analyze how the philosopher understands emotional intuition and subconsciousness. I argue that Sesemann’s approach is phenomenological.
Keywords: Sesemann; phenomenology; consciousness; self-consciousness; objectification; emotional intuition